NVP‐BHG712: Effects of Regioisomers on the Affinity and Selectivity toward the EPHrin Family. (20th July 2018) - Tröster, Alix; Heinzlmeir, Stephanie; Berger, Benedict‐Tilman; Gande, Santosh L.; Saxena, Krishna; Sreeramulu, Sridhar; Linhard, Verena; Nasiri, Amir H.; Bolte, Michael; Müller, Susanne; Kuster, Bernhard; Médard, Guillaume; et al.
Abstract: Erythropoietin‐producing hepatocellular (EPH) receptors are transmembrane receptor tyrosine kinases. Their extracellular domains bind specifically to ephrin A/B ligands, and this binding modulates intracellular kinase activity. EPHs are key players in bidirectional intercellular signaling, controlling cell morphology, adhesion, and migration. They are increasingly recognized as cancer drug targets. We analyzed the binding of NVP‐BHG712 (NVP) to EPHA2 and EPHB4. Unexpectedly, all tested commercially available NVP samples turned out to be a regioisomer (NVPiso) of the inhibitor, initially described in a Novartis patent application. They only differ by the localization of a single methyl group on either one of two adjacent nitrogen atoms. The two compounds of identical mass revealed different binding modes. Furthermore, both in vitro and in vivo experiments showed that the isomers differ in their kinase affinity and selectivity. Abstract : Small change, big difference : A modification in the substitution pattern of the published kinase inhibitor NVP‐BHG712 from Novartis leads to different binding modes as well as binding affinities toward EPH receptor tyrosine kinases. Additionally, the selectivity profiles of the two compounds for binding to kinases are substantially changed.